A Review of Secure Pub Sub System - Kshirsagar, Padmavati N.; Pratap singh, S.; Sarode, Milindkumar V. (Asian Journal of Electrical Sciences, 2014)
In content-based publish subscribe system authentication and confidentiality are most challenging security issues. This paper presents a novel way to provide confidentiality and authentications in a broker-less contentbased publish subscribe system. The authentication of publishers and subscribers is done using pairing based cryptography. Confidentiality of events is also ensured, by adapting the pairing-based cryptography mechanisms. This paper contributes; secure communication between publisher and subscribers. Publisher use public key to encrypt message, publisher send that message along with its unique identity. To successfully decrypt the message; a receiver needs to obtain a private key for its identity from the key server. The overall approach provides fine-grained key management. Published events are routed to their corresponding subscribers. The evaluation of this project provides security respect to 1) authentication and confidentiality of event dissemination. 2) The overall approach provides fine-grained key management. Published events are routed to their relevant subscribers. The evaluation of this project provides security respect to throughput of the proposed cryptographic primitives.